Role of autophagy in tumor response to radiation: Implications for improving radiotherapy - Roy, Amrita; Bera, Soumen; Saso, Luciano; Dwarakanath, Bilikere S. (Frontiers in Oncology, 2022)
Autophagy is an evolutionary conserved, lysosome-involved cellular process that facilitates the recycling of damaged macromolecules, cellular structures, and organelles, thereby generating precursors for macromolecular biosynthesis through the salvage pathway. It plays an important role in mediating biological responses toward various stress, including those caused by ionizing radiation at the cellular, tissue, and systemic levels thereby implying an instrumental role in shaping the tumor responses to radiotherapy. While a successful execution of autophagy appears to facilitate cell survival, abortive or interruptions in the completion of autophagy drive cell death in a context-dependent manner. Pre-clinical studies establishing its ubiquitous role in cells and tissues, and the systemic response to focal irradiation of tumors have prompted the initiation of clinical trials using pharmacologic modifiers of autophagy for enhancing the efficacy of radiotherapy. However, the outcome from the Phase I/II trials in many human malignancies has so far been equivocal. Such observations have not only precluded the advancement of these autophagy modifiers in the Phase III trial but have also raised concerns regarding their introduction as an adjuvant to radiotherapy. This review captures the current understanding of the interplay between biological responses to radiation damage and autophagy and provides insight into the potential and limitations of targeting autophagy for improving the radiotherapy of tumors.